Development and attestation of a standard sample of calcium nadroparin - A. V. Zykova; S. V. Krivoshchekov; D. A. Isakov; A. M. Guryev; M. V. Belousov (Разработка и регистрация лекарственных средств)
Introduction. The widespread use of heparin preparations for the treatment and prevention of venous thromboembolic complications is known. One of the low molecular weight heparin drugs successfully used in clinical practice is calcium nadroparin. The modern approach to assessing the quality of medicines involves the use of standards, in comparison with which the quality control of the drug is carried out – standard samples (SS). The most important specific parameter in assessing the authenticity of low molecular weight heparins is the characteristic of the fractional composition.Aim. The aim of the work was to develop, attestation and determine the stability during the shelf life of a secondary standard sample to determine the authenticity of calcium nadroparin as part of improving the quality control system of the enterprise with the prospect of creating a domestic pharmacopoeia standard sample.Materials and methods. The object of development and attestation was the standard sample of the enterprise – low molecular weight heparin, obtained on the basis of the Technology implementation center of Siberian state medical university. The certified standard sample was obtained by purification of calcium nadroparin by solid-phase extraction. The completeness of the purification was confirmed by comparing the chromatograms of the purified samples with the chromatograms of the international standard sample. The characteristics of the molecular weight distribution were determined chromatographically. The stability of the certified SSE (the standard sample of the enterprise) was studied under two storage conditions – at a temperature below 8 °C in a dry state for 16 months and in solution at –40 °C for 6 months by evaluating trends in molecular weight distribution.Results and discussion. For each batch of the certified standard sample, the molecular weight and molecular weight characteristics are calculated in 2 parallel definitions, and a representative chromatogram is presented. The values of the relative standard deviation of the molecular weight of the samples and the content of the controlled fractions did not exceed 2.5 %. A detailed analysis of the molecular weight distribution showed the "classical" dependence of RSD (relative standard deviation) from the average value with a significant increase up to 30 % for small fraction values (less than 0.5 %). It was found that during 16 months at a storage temperature below 8 ºC, the molecular weight and molecular weight characteristics of standard samples of low molecular weight heparin did not significantly change. However, in the SSE solution at a storage temperature of minus 40 °C for 6 months, they degraded by more than 10 %.Conclusion. According to the results of the study, a protocol has been developed for obtaining a standard sample of low-molecular-weight heparin for the standardization of the calcium nadroparin substance according to the indicator "molecular weight distribution". The established shelf life of the sample is at least 16 months at temperatures below 8 °C. The stability of solutions of the standard sample at a storage temperature of –40 °C for 3 months is shown.